Frailty and Sarcopenia Onset, Development and Clinical Challenges - Dionyssiotis, Yannis (IntechOpen, 2017)
Frailty is considered a multisystem impairment that makes an individual vulnerable to external or internal stressors. Sarcopenia, the age-dependent loss of muscle mass and function, is proposed as the biological substrate and the pathway whereby the consequences of physical frailty develop. These syndromes are associated with a negative impact in quality of life and can lead to the occurrence of disability, institutionalization, and even mortality. The book focuses upon all the related aspects of frailty and sarcopenia and the new advancements in the related treatments including complex issues and research. It includes high-quality chapters in all related aspects for the syndromes of sarcopenia and frailty, which adversely affect the function and overall effectiveness of the musculoskeletal system and interventions to promote rehabilitation.